PSYCHOLOGICAL DIMENSIONS AND SOC AMONG ELDERLY PRIMARY CAREGIVERS PROVIDING HOME CARE FOR ELDERLY - Ninomiya, S. (Innov Aging, 2017)
Objective: The present study surveyed the elderly primary caregivers providing home-based care for elderly individuals in local regions of Japan in order to determine whether psychological dimensions and sense of coherence (SOC) differed according to age group. Methods: The subjects were 67 pairs comprised of elderly individuals aged ≥65 years undergoing home care and their primary caregivers also aged ≥65 years. The survey items consisted of primary caregiver attributes, Barthel Index (BI), psychological dimensions (mental health; CES-D8), feeling of caregiving burden (J-ZBI), general self-efficacy (GSES), life satisfaction (LSI-K), and SOC (SOC13-5). For comparison, primary caregiver responses were scored and classified into two age groups: 65–74 years and ≥75 years. The survey was designed to avoid any potential ethical issues. Results: SOC was significantly higher among primary caregivers aged ≥75 years than those aged 65–74 years. Positive correlations between GSES, LSI-K and SOC were recognized in both age groups. A negative correlation in the J-ZBI, CES-D8 and SOC scores was only seen among the primary caregivers aged ≥75 years. Discussion: Primary caregivers who had a high SOC score exhibited a high level of general self-efficacy and life satisfaction. The results also suggested that primary caregivers aged ≥75 years who had a high SOC score had a low feeling of caregiving burden and a high level of mental health. Primary caregivers aged ≥75 years had a higher SOC than their 65–74 year-old counterparts, suggesting that a high level of SOC is important in continuing to provide care.